The effect of use of electronic money (funds) on students' consumptive behavior - Sugeng, Rachmat; Putri, Andi Sulfiana Eka (Junal Ilmu Manajemen, 2025)
This study aims to explore how the use of electronic money affects the consumptive behavior of Management students in the Management Study Program at Fajar University, Makassar. It employs a quantitative research approach. The study's population consists of Management students from the 2019, 2020, and 2021 cohorts at Fajar University, totaling 391 students, with a sample size of 80. Purposive sampling was used for data collection, which was carried out through a questionnaire (Google Form), and the data were analyzed using simple linear regression. The findings indicate a positive but weak and minimal impact of electronic money usage (DANA) on the consumptive behavior of students, with convenience being a contributing factor. However, the adoption of DANA is not widely favored by students, particularly for transactional purposes. Additionally, other factors not included in this study, such as benefits, promotions, attitudes toward usage, risks, and service features, may also influence this behavior.